TEKNIK MANAJEMEN SUMBER DAYA MANUSIA YANG EFEKTIF DI ERA BISNIS MODERN UNTUK MENINGKATKAN KINERJA PEGAWAI - Wirati Adriati, I Gusti Ayu; Sariani, Ni Luh Putu (Jurnal Magister Manajemen, 2024)
The objective of this study is to enhance employee performance by investigating efficient human resource management (HR) tactics within the dynamic framework of the worldwide corporate environment. This study employs a case study methodology and qualitative techniques. The population of the research includes all employees in the specific organization, with a sample consisting of individuals with varying levels of experience in HR management. Document review, direct observation, and in-depth interviews are examples of research instruments. The findings of the study demonstrate that thorough hiring and selection provide a strong basis for long-term productivity, and ongoing training and development improves workers' ability to adjust to changing work conditions. A transparent and productive work environment is produced by effective communication, and a work culture that emphasizes growth and higher success and improves employee performance is created by providing constructive feedback. Increased productivity, a healthy work-life balance, motivation, engagement, career development, and efficient performance management are all impacted by HR management methods on employee performance. Through the identification of critical variables influencing employee performance and the development of corresponding strategies, this research offers businesses direction and suggestions for navigating the intricacies of the contemporary business environment and achieving sustained success